2019
DOI: 10.1155/2019/5323428
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Immunogenicity and Safety of Two Pediatric TBE Vaccines Based on the Far Eastern and European Virus Subtypes

Abstract: Up to 10,000 cases of tick-borne encephalitis are registered annually, 20% of which occur in children under 17 years of age. A comparison of the immunogenicity and safety between a new pediatric Tick-E-Vac vaccine based on the TBEV strain Sofjin and FSME-IMMUN Junior vaccine was performed in the Sverdlovsk region. The vaccine strains differ from strains of the Siberian subtype of TBEV that dominates in the region. The study was performed on 163 children aged 1 to 15, who received one of the vaccines according … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Available TBEV vaccines were developed over 30 yr ago and consist of inactivated virus grown on chick embryo cells. Vaccination is TBEV specific, requires priming and two boosts, and results in 90-100% seroconversion depending on the vaccine used (Loew-Baselli et al, 2009;Maikova et al, 2019;Vorovitch et al, 2019). Additional boosts are recommended every 3-5 yr for the lifetime of the individual.…”
Section: Discussionmentioning
confidence: 99%
“…Available TBEV vaccines were developed over 30 yr ago and consist of inactivated virus grown on chick embryo cells. Vaccination is TBEV specific, requires priming and two boosts, and results in 90-100% seroconversion depending on the vaccine used (Loew-Baselli et al, 2009;Maikova et al, 2019;Vorovitch et al, 2019). Additional boosts are recommended every 3-5 yr for the lifetime of the individual.…”
Section: Discussionmentioning
confidence: 99%
“…In general, European and Russian TBEV vaccines are considered safe and well tolerated. However, mild to moderate systemic and local adverse effects, such as fever, headache or redness and swelling at the injection site, can appear both in children and adults [ 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ].…”
Section: Currently Available Vaccinesmentioning
confidence: 99%
“…All TBEV vaccines are highly immunogenic with high and fast seroconversion rates ranging from 86–100%, depending on the TBEV vaccine, evaluation method and study design. Various studies showed seropositivity levels of 99.1–100% for the European vaccines after complete primary immunization [ 49 ], 100% for the Russian vaccines after two immunizations [ 51 , 52 ] and 86–96% for the Chinese vaccine after two vaccinations (reviewed in [ 37 , 53 ]). In general, waning of the vaccine-induced immunity over time has been reported in several studies [ 49 , 54 , 55 , 56 , 57 ].…”
Section: Currently Available Vaccinesmentioning
confidence: 99%
“…In the Russian Federation, more than 60 million people live in TBE-endemic regions and 2000-3000 cases of the disease are registered annually. 3 Prophylactic vaccination is the most effective form of protection against TBE. Currently on the market, there are six inactivated TBE vaccines based on the European and Far Eastern TBEV strains.…”
Section: Introductionmentioning
confidence: 99%
“…In the Russian Federation, more than 60 million people live in TBE-endemic regions and 2000–3000 cases of the disease are registered annually. 3 …”
Section: Introductionmentioning
confidence: 99%